64 nm continuously tunable graphene-mode-locked erbium-doped fiber laser by tunable bandpass filter - Muhammad, Farah Diana; Azis, Raba'ah Syahidah; Ahmad, Fauzan (Institute of Physics, 2025)
This paper demonstrates and characterizes a tunable wavelength ultrafast erbium-doped fiber laser, enabled by a tunable bandpass filter and mode-locked with a graphene thin film as the saturable absorber. The laser's wavelength can be continuously tuned from 1507.5 nm to 1571.3 nm, covering a broad range of 63.8 nm. Fourteen distinct wavelengths, spaced at 5 nm intervals, are recorded. The variation in bandwidth and pulse width across these wavelengths reveals values ranging from 0.5 nm to 0.8 nm and from 3.9 ps to 6.6 ps, respectively, all at a fixed repetition rate of 12.9 MHz. Analysis of the time-bandwidth product shows a lowest value of 0.34 at 1567.5 nm and a highest value of 0.46 at 1507.5 nm. These findings enhance the understanding of wavelength-tunable graphene-based mode-locked erbium-doped fiber laser operation, specifically through the spectral filtering effect achieved with a tunable bandpass filter.